GOSSEC: Goal Oriented Software Sustainability Evaluation Criteria (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The concepts of sustainability is now aware among the software engineering researchers.  It has direct and indirect impacts on three dimensions which are environment, economic and social that results from the development and implementation of the software. Although there are studies on software sustainability evaluation that defines the software sustainability criteria unfortunately, most of the studies are focusing on single criterion rather than come out with holistic criteria of software sustainability. Additionally, the studies also focused on what need to be measured instead of how to perform the evaluation systematically. This limitation was occurred due to lack of defining the measurement goal of each criteria of software sustainability dimensions. Therefore, this study aimed to develop a Goal Oriented Software Sustainability Evaluation Criteria and organize the sustainability criteria using Quality Function Deployment. On top of that, the Goal Oriented Software Sustainability Evaluation Criteria has been constructed using Goal Oriented Measurement approach by adapting the Goal Question Metric method to assist in defining the goal that clearly defined the purposes, perspectives, and point of views of measurement of software sustainability. Hence, the Goal Oriented Software Sustainability Evaluation Criteria provides nine (9) goals and thirty four (34) sub goals for measuring the software sustainability criteria and sub criteria. The findings from the study present a set of criteria and measurement goals which can be used for evaluating software sustainability. The criteria were organized into three dimensions which are environment, economic and social.